A Decision Making Model for the Evaluation of Supply Chain Execution and Management Systems - VAYVAY, ÖZALP (ATLANTIS PRESS, 2013)
A Supply Chain Execution and Management (SCEM) system is an enterprise application that integrates all of the necessary supply chain functions into a single system. These functions range from common ones such as warehouse and transportation management to less known ones such as demand management. In order to execute and manage the supply chain processes successfully, organisations need a comprehensive evaluation approach to determine the most suitable system. The evaluation of an SCEM system involves numerous decision making criteria. Moreover, it is usually characterised with uncertainty and vagueness since it is very difficult to rate SCEM system alternatives with exact terms. To cope with this problem, a fuzzy logic-based approach is developed in this study. This approach main integrates the Fuzzy Analytic Hierarchy Process to weight the decision criteria and the Fuzzy Technique for Order Preference by Similarity to Ideal Solution to rate alternatives. A real life example is provided to demonstrate the capability of the proposed approach.
Keywords: Supply Chain Execution and Management System; F-MADM; F-AHP; F-TOPSIS; BUSINESS